Chronic Kidney Disease, Obesity, and Hypertension: The Role of Leptin and Adiponectin - M. Tesauro; A. Mascali; O. Franzese; S. Cipriani; C. Cardillo; N. Di Daniele (International Journal of Hypertension)
Chronic kidney disease is a major public health problem and characterized by a progressive loss in renal function over a period of months or years as defined by structural or functional abnormalities of the kidney. Several elements contribute to determine a progression of the kidney injury, inducing a worsening of renal damage and accelerating the decline of renal function: obesity and hypertension are two known factors of kidney progression. Remarkable improvements have been recently achieved in the study of the endocrine features of the adipose tissue and have been able to produce hormone-like peptides named adipokines or adipocytokines. Among these adipocytokines, which represent a link between obesity, hypertension, and chronic nephropathy, leptins and adiponectin appear to play an important role. Leptin not only is a prohypertension element (renal progression factor) through the activation sympathetic nervous, but also is able to induce prosclerotic effects directly on the kidney. In contrast, a decline of adiponectin levels has been shown to be related to a picture of hypertension: an endothelial dysfunction has been described as the main pathogenic mechanism responsible for this phenomenon.